SYSTEMATIC LITERATURE REVIEW Upaya Peningkatan Kemampuan Berpikir Kreatif Pada Pembelajaran Matematika Siswa SMP: 3.1 Penemuan Unik dan Kesesuaian dengan Penelitian Lain, 3.2 Faktor Internal: Kepercayaan Diri dan Kecerdasan Intrapersonal - Iryanto, Rizal; Kurniati, Nani; Anwariyah, Sofiyatil; Thohira, Nur (Journal of Science Technology and Education, 2025)
This study aims to analyze the learning strategies that have been implemented to improve the creative thinking skills of junior high school students in mathematics. The method used is a Systematic Literature Review of nine relevant scientific journals from 2018 to 2025. The results of this study show that the application of contextual approaches such as realistic mathematics, cooperative models such as Think Pair Share, and innovative learning media such as E-comics, regenerative STEM, and KOLANG comics have proven to be effective in developing creative thinking indicators, namely fluency, flexibility, originality, and elaboration. In addition, internal student factors such as self-confidence and intrapersonal intelligence also play an important role in the creative thinking process. It was concluded that the combination of contextual learning, innovative media, and psychological factor support is the key to success in increasing the mathematical creativity of junior high school students.